The impact of functional empowerment on organizational agility in Jordanian insurance companies - Al-Majali, Amira AbdulWahhab; Bani Hamdan, Khaled Mohammed (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aimed to identify the impact of empowerment in its dimensions (delegation of powers, motivation, training, participation in decision-making) on organizational agility with its dimensions (sensing agility, decision-making agility, agility of practice) in insurance companies in Jordan. The study used the analytical description methodology, which is based on determining the characteristics of the phenomenon, describing its nature and the quality of the relationship between its variables, causes and trends. The study sample consisted of (250) employees from (5) companies, with (50) employees from each company. After completing the process of collecting data for the variables required for the study, they were entered into the statistical software to obtain the results related to answering the study questions, and some statistical methods available in the Statistical Packages for Social Sciences (SPSS) programs were applied with the aim of statistically processing the data. The study found an impact of functional empowerment in its dimensions (delegating authority, motivation, training, participation in decision-making) in organizational agility with its dimensions (sensing agility, decision-making agility, agility of practice) in insurance companies in Jordan. The study concluded by recommending the necessity of granting employees a delegation of powers in order to complete their work appropriately, the necessity of implementing training courses for employees in dealing with various crises, and the need for company departments to pay attention to conducting educational seminars and lectures on the importance of organizational culture (agility of sensing, agility of practice, agility of decision-making). , because of its role in raising the levels of performance.